Estudo sobre fatores envolvidos no processo de utilização da modalidade de compra clique e retire, a partir da Teoria Unificada de Aceitação de Tecnologia UTAUT2 e o impacto da conveniência em um ambiente de varejo omnichannel - Edilson Christian de Lima Manduca (2023)
Click-and-collect purchasing is one of the many ways that e-commerce offers customers to purchase products without having to leave home. This modality allows the customer to buy online and collect the product in the physical store or pick it up at a physical pickup point chosen by them, depending on availability, without shipping costs, with greater agility in the delivery process and convenience. The relationship between convenience and the adoption of click-and-collect purchasing can be complex, as other factors, such as product availability and quality of service, can also affect consumers' purchasing decisions. It is worth highlighting in this relationship the role of digital functionality and its impact on consumer purchasing intentions. In this sense, the UTAUT2 Model presents itself as a theoretical approach that can be applied to understand the factors that influence the adoption of click-and-collect purchasing in an omnichannel retail environment. The model proposes that the intention to use a technology is determined by performance expectations, perceived effort, social influence and facilitating conditions. Seeking to capture even more nuances and factors that influence reach, use of technologies and especially convenience, an extension of the UTAUT2 model was proposed. The general objective of this research is to measure the impact of convenience on the intention to use the click-and-collect purchasing method using an extended model of the Unified Theory of Acceptance of Technology Extended (UTAUT2). The specific objectives are: To compare the UTAUT2 and UTAUT2 models with the addition of convenience, evaluating whether the inclusion of the convenience construct increases the explanatory capacity of customers' behavioral intention in relation to the use of Click and Collect; To adapt the UTAUT2 questionnaire to the context of the use of the click and collect purchase modality; To evaluate which antecedent constructs are significant in explaining the Intention to Use and the Behavior of Using Click and Collect; To extend UTUAT2 with the convenience constructs and identify which types of convenience have the greatest impact on behavioral intention.. To check the usage intention and usage behavior of consumers and it was empirically tested on a sample of 540 consumers and the responses are tested using PLS-SEM as a testing method. The evidence suggests that Hedonic Motivation and processing convenience are relevant to intention to use. Contrary to what was expected, the hypotheses that convenience of access and digital convenience, despite being significant at 5%, had a negative impact on the intention to use. The other hypotheses were all corroborated in our model. The variables performance expectation and relational convenience have greater relevance in intention to use, with, respectively, weights of 28.4% and 24.0%. We also highlight the impact of the variables effort expectation, facilitating conditions and habit with a medium influence on the intention to use, while the variables functional convenience, social influence and price value have a statistically significant impact. Finally, the variables hedonic motivation and process convenience were not statistically significant on the intention to use. The main contributions of this work were to test the impact of convenience types on usage intention for the click-and-collect context, so that the only convenience type that was significant for this model was relational, contrasting with some previous studies and advancing retail theory. In addition, from a managerial point of view, this work contributes to managers' understanding of which aspects they should prioritize investing in within the click-and-collect modality.